Scalable and Sustainable Blockchain: Architecting Infrastructure and Developing a Platform for Efficient Management and Exploration - Pedro Silva; Tiago Guimaraes; Ricardo Duarte; Manuel Filipe Santos (IEEE Access)
The application of blockchain technology in the health and healthcare sector is considered disruptive, thus requiring trust, integrity, and value of data. In addition, this document analyses the potential of permissioned blockchain, more specifically Hyperledger Fabric, to improve the security, integrity, and efficiency of healthcare systems. It examines ways in which this can be done in a manner that has both scalability and sustainability prospects in the long-term. This, by reaching the optimal compromise between efficiency of resources and its ease of use, management and upscaling. The ability to be as lightweight as possible, while being able to quickly expand the infrastructure and seamlessly integrate new functionalities, maintaining operational efficiency. The research developed involves a review of the literature, the development of three different blockchain implementations/architectures: one based on Docker, another based on Kubernetes and, finally, one based on Kubernetes with a load balancer. Where the practical assessment of performance metrics is performed. The evaluation revealed that Docker is particularly suitable for smaller environments, thanks to its faster configuration and lower resource consumption, making it ideal for development, proof of concept and testing phases. On the other hand, Kubernetes stood out for its significant advantages in terms of scalability, managing increased load and traffic efficiently, particularly in larger environments and production scenarios. Finally, a blockchain management and monitoring platform is presented. This was developed to ensure long-term usability and maintenance of blockchain solutions in the healthcare industry. This work aims to advance the application of blockchain in healthcare, addressing both immediate and long-term needs for security and efficiency.